The Economic-Financial Crisis 2007 – 2009 - Andreea Nicoleta Donici; Alexandra Diaconu (CES Working Papers, 2010)
This article takes a look at the well known economical and financial crisis, which affected all the countries in the world. When comes to Europe, the most affected countries were the Baltic countries: Estonia, Latvia and Lithuania. The economy of these countries shrank enough, so that they cope with another wave of crisis.
Keywords: 330; financial crisis; irrational exuberance; Baltic countries